DURABILITY OF REINFORCED CONCRETE PILES IN AGGRESSIVE SOIL CONDITIONS - K. Maxsimov (Journals Park Publishing, 2023)
A method is given for determining the bearing capacity of driven piles in aggressive soil conditions. The shear resistance f0 of concrete corrosion products and the resistance of piles Фk in the area of possible corrosion damage to concrete were determined. Taking into account the influencing factor of the corrosion process on the bearing capacity of piles in medium, highly aggressive environments, primary and secondary protection of piles have been proposed.
Keywords: saline soils, soil resistance along the lateral surface of the pile, concrete corrosion, predicted corrosion depth, impregnating compositions, sulfate-resistant рortland cement.